Manajemen Risiko Investasi Wakaf Uang - Rozalinda, Rozalinda (ISLAMICA: Jurnal Studi Keislaman, 2012)
This paper is aimed at discussing the notion of endowment as a form of investment. Like any other kinds of investment, endowment needs a proper management especially that which is related to risk. Hence, the subject of this paper is risk management for money endowment, i.e., endowment in the form of money. A lack of proper management will certainly lead to the unsuccessful investment such as the ineffective cash-flow which occurs as a result of inflation. The paper argues that the unsuccessful endowment is often the victim of its own ineffective management, or else of its inefficient managers. Many endowments have no managers and management, the result of which being that it cannot be sustained and made use of. While the Syariâah banking has improved dramatically in many Muslim countries, and has been run professionally, the paper asks, why is it not the case with the endowment sector?